China and ASEAN : energy security, cooperation and competition - Zhao, Hong (Singapore : ISEAS Yusof Ishak Institute, 2015)
This book examines the energy resource relations between China and ASEAN countries. It addresses the following issues: as the world energy demand shifts East because of the rise of China, ASEAN community and other emerging Asian economies, and as the Greater Indian Ocean and the South China Sea become the world's energy interstates, will geopolitical tensions over energy resources spark conflicts in the region, especially in the South China Sea? Against the background of China's rise and its growing influence in Southeast Asia, will China's quest for energy resource cooperation be viewed as a threat or opportunity by its neighbouring countries? Since the United States, Japan and India are important players in Southeast Asia, does the shifting geopolitics of energy give these big powers a new strategic tool in an intensifying rivalry with China? Or does the changing geopolitics of energy resources create more areas of shared interests and opportunities for cooperation between these big powers to balance, rather than increase, tensions in Southeast Asia? This book will be of interest to anyone who is keen to learn how the world, especially the United States, can accommodate and adapt to the new global energy dynamics and how China and ASEAN operate as new players in global and regional energy markets.
Title from publisher's bibliographic system (viewed on 05 Jun 2017).
Keywords: Energy policy -- China; Energy policy -- Southeast Asia; Energy consumption -- China; Energy consumption -- Southeast Asia; Southeast Asia -- Foreign relations -- China; Southeast Asia -- Foreign economic relations -- China; China -- Foreign relations -- Southeast Asia; China -- Foreign economic relations -- Southeast Asia